Association of IGF1 single-nucleotide polymorphisms with myopia in Chinese children - Cheng, Tianyu; Wang, Jingjing; Xiong, Shuyu; Zhang, Bo; Li, Qiangqiang; Xu, Xun; He, Xiangui (PeerJ (San Francisco, CA), 2020)
To investigate the association between insulin-like growth factor 1 ( ) single-nucleotide polymorphisms (SNPs) and myopia in a young Chinese population. A total of 654 Chinese children aged 6-13 years from one primary school participated in our study and underwent a series of comprehensive ocular examinations, including cycloplegic refraction and measurements of axial length. Myopia was defined as a spherical equivalence (SE) ≤ -0.5 D in the worse eye. In total, six tagging SNPs of were genotyped using the PCR-LDR (Polymerase Chain Reaction-Ligation Detection Reaction) method. We tested four different genetic modes (the allele, dominant, recessive, and additive models) of these SNPs and used multivariate logistic regression to calculate the effect of SNPs on myopia. In addition, we conducted a haplotype analysis with a variable-sized slide-window strategy. Overall, 281 myopic children and 373 non-myopic controls were included in the analysis. The SNP rs2162679 showed a statistical difference between the two groups in both the allele ( = 0.0474) and additive ( = 0.0497) models. After adjusting for age and gender, children with the genotype AA in the SNP rs2162679 had a higher risk of myopia than those with the genotype GG (OR = 2.219, 95% CI [1.218-4.039], = 0.009). All haplotypes that varied significantly between the two groups contained the SNP rs2162679, and the four-SNP window rs5742653-rs2162679 had the lowest value (Chi square = 5.768, = 0.0163). However, after permutation tests, none of the associations remained statistically significant. The SNP rs2162679 in was associated with myopia in a young Chinese population. The G allele in the SNP rs2162679 may protect against myopia.